2019
DOI: 10.1103/physreva.100.062130
|View full text |Cite
|
Sign up to set email alerts
|

Sharing nonlocality and nontrivial preparation contextuality using the same family of Bell expressions

Abstract: In [Phys. Rev. Lett. 114, 250401 (2015)] the sharing of non-locality by multiple observers was demonstrated through the quantum violation of Clauser-Horne-Shimony-Halt inequality. In this paper we provide a scheme for sharing of non-locality and non-trivial preparation contextuality sequentially through the quantum violation of a family of Bell's inequalities where Alice and Bob perform 2 n−1 and n numbers of measurements of dichotomic observables respectively. For this, we consider that Alice always performs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 24 publications
(46 reference statements)
0
51
0
Order By: Relevance
“…Since the presence of non-locality implies the possibility of steering and the presence of entanglement, our work shows that it is also possible to achieve both of these with arbitrarily many independent Bobs using only a single pair of entangled qubits. This goes against some of the results in [18,22,23], and suggests that it is worth rethinking others that study the space of such correlations [24] or look at other Bell in-equalities [25] or more parties [26,27] after removing the assumption that both measurements used by each party have the same sharpness.…”
Section: Discussionmentioning
confidence: 98%
“…Since the presence of non-locality implies the possibility of steering and the presence of entanglement, our work shows that it is also possible to achieve both of these with arbitrarily many independent Bobs using only a single pair of entangled qubits. This goes against some of the results in [18,22,23], and suggests that it is worth rethinking others that study the space of such correlations [24] or look at other Bell in-equalities [25] or more parties [26,27] after removing the assumption that both measurements used by each party have the same sharpness.…”
Section: Discussionmentioning
confidence: 98%
“…(12) when the dimension of the system is lower than that is required for achieving the optimal quantum value (B n ) opt Q . One of us have shown [39] that the sharing of preparation contextuality can be demonstrated by arbitrary number of Bobs by using optimal quantum value (B n ) opt Q for d = 2 n/2 dimensional Hilbert space. Here, by providing the examples of n = 5 and n = 6, we have demonstrated that even for lower dimensional system the number of Bobs who can share the preparation contextuality remains same but the value of unshrapness parameter required is always higher in lower dimensional system.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…x 1 and y i x 2 by invoking the encoding scheme used in Random Access Codes (RACs) [43][44][45][46] as a tool. This will fix 1 or −1 values of (−1) y i x 1 and (−1) y i x 2 in Eq.…”
Section: Generalized Bilocality and N-locality Scenario In Star-netwo...mentioning
confidence: 99%